The microstructural origin of rapid densification in 3YSZ during ultra-fast firing with or without an electric field - Ji, W; Zhang, J; Wang, W; Fu, Z; Todd, R (Elseveir, 2020)
Recent research has shown that very rapid heating of 3YSZ powder compacts (ultra-fast firing), whether by passing an electric current through the sample (flash sintering) or by using external heat sources, causes a great acceleration of densification rate for a given relative density and temperature. Here, the microstructural evolution of 3YSZ is studied using four sintering methods with widely differing heating rates, produced with or without electric fields. The microstructural development depended greatly on thermal history. Most significantly, slow, conventional heating resulted in pores much larger than the grain size, whereas most pores were smaller than the grain size with the rapid heating methods, whether the heating involved an electric field or not. The smaller pore size clearly provides a major contribution to the acceleration of densification following rapid heating. In contrast, grain growth was not suppressed by rapid heating but was suppressed by an electric field.